학사지도 교육프로그램 운영 및 성과 -동국대학교 파라미타칼리지 사례를 중심으로 - 김지용; 강성배 (교양교육연구, 9(2), 2015)
최근 한국 대학들은 학령인구 감소로 인한 신입생 충원, 재학생들의 중도 이탈 및 신입생의 교육방향 문제에 대해 많은 고민을 갖게 되었고, 이를 해결하기 위한 다양한 프로그램을 도입하고 있다. 특히 지방 소재 대학들은 학생들의 학업성취도 문제와는 별개로, 재학생의 학업 유지율과 졸업생 비율의 증대에 보다 많은 관심을 기울 수밖에 없는 현실이다. 따라서 동 사안에 대하여 서울 소재 대학들에 비해 더 많은 고민을 할 수 밖에 없는 처지에 있는 지방 소재 대학들은 대학 신입생에 초점을 맞춘 학사지도교육 프로그램에 주목하지 않을 수 없게 되었다. 본 연구에서는 상기와 같은 문제의식 하에, 동국대학교 파라미타칼리지에서 2014년 1학기 도입한 학사지도 교육프로그램을 소개하고, 한 학기 동안의 운영현황 및 성과 그리고 개선방안에 대해 사례를 중심으로 논의하고자 한다. 또한, 동국대학교 신입생들의 교양필수교과목인「대학생활과 자기계발 Ⅰ,Ⅱ」와 교수/학생 간 1:1 심층면담의 결과가 신입생들의 학교생활 적응과 대학 공부에 어떤 영향을 미쳤는지에 대한 성과도 분석하고자 하였다. As a part of new student administration, importance of academic advising building up recently. The academic advising, along with the academic structure and academic curriculum, is one of the three critical components of the undergraduate education in American colleges an universities. Academic advising is an opportunity to exchange information designed to help students reach their educational and career goals. To enhance the quality of freshmen education, Dongguk University at Gyeongju established PARAMITA College and introduced academic advising program since March, 2014. The purpose of this study reviews present conditions and examines outcomes running by academic advising program in PARAMITA College. Primary features of academic advising program in PARAMITA College are culture mandatory course, "Campus Life & Self-improvement 1, 2 " taught by academic advisor and also new student should be obliged to take one face-to-face talk with academic advisor in semester. Main results of this study are as follows : Through take academic advising course and face-to-face talk, students will be able to more actively explore reasons to study, what to learn, and what they need to improve themselves, and to search their career path. KCI Citation Count: 10